Protection of Stone Building Structures Against Corrosion Caused by Moisture - Teresa Szymura; Danuta Barnat-Hunek (Barometr Regionalny)
The paper aims to present the most important issues concerning the nature of protection of masonry materials against moisture. The paper describes the parameters which influence the effectiveness of these protection methods such as porosity, salinity, and surface state. Special attention is devoted to the ecological aspect of hydrophobizing preparations available on the market. Also technical criteria and practical advice for the use of these preparations to prevent damage are extensively discussed in the paper.